2011
DOI: 10.1016/j.jtcvs.2010.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of surgical techniques for early-stage thymoma: Feasibility of minimally invasive thymectomy and comparison with open resection

Abstract: VATS of early-stage thymoma appears safe and feasible and was associated with a shorter hospital stay. The oncologic outcomes were comparable in the open and VATS groups during intermediate-term follow-up. Additional follow-up is required to evaluate the long-term results of thoracoscopic thymectomy for early-stage thymoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
79
3
5

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(97 citation statements)
references
References 28 publications
(35 reference statements)
10
79
3
5
Order By: Relevance
“…The mean hospital stay in this study was 4.0 days compared to 4.3 days in our study. As for the comparisons between the VATS group and MS group, our data were also consistent with published studies (18)(19)(20).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The mean hospital stay in this study was 4.0 days compared to 4.3 days in our study. As for the comparisons between the VATS group and MS group, our data were also consistent with published studies (18)(19)(20).…”
Section: Discussionsupporting
confidence: 91%
“…It has been reported that for the treatment of stage I and II thymomas, there were no significant differences in the 5-year survival, 5-year recurrence-free survival (19), or mean survival time (4) between the VATS group and open surgery group. In addition, robots have more technical advantages with three-dimensional vision systems and multi-articulated instruments, which allows an open-like intervention, while robotic extended thymectomy has been shown to be feasible and safe (22,23).…”
Section: Discussionmentioning
confidence: 92%
“…Thymectomy done for early-stage (stages I and II) TETs ( Figure 2) through minimally invasive approaches also appears to be both feasible and safe (13)(14)(15)(16). Proponents of this strategy argue that such approaches are associated with less operative trauma and chest wall disruption, reduction in pulmonary or other morbidities, reduction in postoperative pain, and shorter length of stay.…”
Section: Controversies In Surgical Managementmentioning
confidence: 99%
“…Also, increased use of CT screening for lung cancer has led to more cases of incidentally detected small lesions at early stage. And advent of minimally invasive surgery in recent years also contributed to increased interest in video-assisted thoracoscopic surgery (VATS) thymomectomy (7). Although some single-center studies have shown no statistical differences in diseasefree survival between thymectomy and thymomectomy, the follow-up durations were relatively short despite of the rarity and the indolent nature of thymomas (2,3).…”
Section: Introductionmentioning
confidence: 99%